Study on the Effect of Alkali Metal Chlorides in Aqueous Solutions of Sodium Carboxymethyl Cellulose using Ultrasound - Raju, K.; Rakkappan, C. (Asian Journal of Chemistry, 2010)
Measurement of ultrasonic velocity, density and viscosity were carried out for the aqueous solutions of sodium carboxymethyl cellulose with various concentrations of sodium chloride, lithium chloride and potassium chloride at different temperatures. The experimental data were used to estimate the ultrasonic parameters like adiabatic compressibility, free length, rao's constant, acoustic impedance, etc. In particular, the ionic hydration numbers for the electrolyte were estimated when the electrolyte is in polymer solutions. The results are interpreted in terms of polymersolvent, polymer-polymer and polymer-ion interactions.